Pharmacogenomic considerations in opioid analgesia - Vuilleumier PH; Stamer UM; Landau R (Dove Medical Press, 2012)
Pascal H Vuilleumier,1 Ulrike M Stamer,1 Ruth Landau21Klinik für Anästhesiologie und Schmerztherapie, Inselspital Universität Bern, Switzerland; 2Department of Anesthesiology and Pain Medicine, University of Washington School of Medicine, Seattle, WA, USAAbstract: Translating pharmacogenetics to clinical practice has been particularly challenging in the context of pain, due to the complexity of this multifaceted phenotype and the overall subjective nature of pain perception and response to analgesia. Overall, numerous genes involved with the pharmacokinetics and dynamics of opioids response are candidate genes in the context of opioid analgesia. The clinical relevance of CYP2D6 genotyping to predict analgesic outcomes is still relatively unknown; the two extremes in CYP2D6 genotype (ultrarapid and poor metabolism) seem to predict pain response and/or adverse effects. Overall, the level of evidence linking genetic variability (CYP2D6 and CYP3A4) to oxycodone response and phenotype (altered biotransformation of oxycodone into oxymorphone and overall clearance of oxycodone and oxymorphone) is strong; however, there has been no randomized clinical trial on the benefits of genetic testing prior to oxycodone therapy. On the other hand, predicting the analgesic response to morphine based on pharmacogenetic testing is more complex; though there was hope that simple genetic testing would allow tailoring morphine doses to provide optimal analgesia, this is unlikely to occur. A variety of polymorphisms clearly influence pain perception and behavior in response to pain. However, the response to analgesics also differs depending on the pain modality and the potential for repeated noxious stimuli, the opioid prescribed, and even its route of administration.Keywords: pain perception, opioid analgesia, genetic variation, pharmacogenetics